Adsorption of Chromium (III) on Melamine: Kinetic, Isotherm, Thermodynamics and Mechanism Analysis. Issue 1 (June 2020) - Guo, Jing; Chen, Ronghua; Zhang, Liuying; Shang, Qian; Chen, Ya; Peng, Hao
Abstract: Melamine as single absorbance had been investigated in heavy metal ions removing and it showed good adsorption performance. This paper focused on the chromium (III) remove from wastewater by adsorption with melamine. The results showed that the melamine had a great adsorption surface area of 8.71 m2/g and high adsorption capacity (2843 mg/g) at removal efficiency of chromium (III) (98.63%) within 60 min at n (melamine)/n (chromium)=1.5 and reaction temperature at 90 °C. The adsorption process was described by Langmuir isotherm and the kinetic process was fitted well with pseudo-second-order model. The adsorption process was a spontaneous, endothermic and physisorption process according to the thermodynamic analyzing results. This study provided a good evidence for successful application of melamine in adsorptive removal of chromium (III) from wastewater.